Impairment of adenosine signaling disrupts early embryo development: unveiling the underlying mechanisms - Glaser, Talita; Martins, Patrícia; Beco, Renata; Bento, Carolina Adriane; Cappellari, Angelica R.; La Banca Oliveira, Sophia; Merkel, Christian Albert; Arnaud-Sampaio, Vanessa Fernandes; Lameu, Claudiana; Battastini, Ana Maria; Ulrich, Henning (Frontiers in Pharmacology, 2024)
Purinergic signaling has been implicated in many biological functions, including development.Here, we investigate the functions of extracellular adenosine and adenosine receptors using a mouse embryonic stem cell (ESC) line and morula stages isolated from mouse embryos. Feederfree mouse ESC was investigated in the absence and presence of LIF, configuring undifferentiated cells and cells undergoing spontaneous differentiation. High alkaline phosphatase (ALPL) and low CD73 levels resulting in low adenosine (eADO) levels were characteristic for pluripotent cells in the presence of LIF, while LIF deprivation resulted in augmented adenosine levels and reduced pluripotency marker expression, being indicative for differentiation. Tracing ESC proliferation by BrdU labeling revealed that inhibition of ALPL by levamisole resulted in a decrease of proliferation due to less eADO accumulation. Further, caffeine and levamisole treatment, inhibiting adenosine receptor and eADO accumulation, respectively, reduced ESC migration, similar to that observed in the absence of LIF. Pharmacological approaches of selective adenosine receptor subtype inhibition triggered specific adenosine receptor activities thus triggering calcium or MAP kinase pathways leading to differentiation. In line with the in vitro data, mouse embryos at the morula stage were sensitive to treatments with A1 and A3 receptor antagonists, leading to conclude that A1 receptor and A3 receptor inhibition impairs proliferation and self-renewal and triggers inappropriate differentiation, respectively. The findings herein define the functions of eADO signaling in early development with implications for developmental disorders, in which adenosine receptors or ectonucleotidase dysfunctions are involved and that could lead to malformations and miscarriages, including under exposure to caffeine.